2018
DOI: 10.26457/recein.v13i49.1510
|View full text |Cite
|
Sign up to set email alerts
|

Personnel selection in complex organizations: A case of Mexican football team for the 2018 World Cup in Russia

Abstract: Selection of personnel in organizations is usually a difficult task. The process gets even more complicated when the selection takes place in complex organizations where different areas can work towards multiple objectives. As many areas might be involved in the selection, the process can become complex and hard to manage. Therefore, it is desirable to use decision-making tools to make the process easier. In this article, we propose new methodology for personnel selection based on Multi-criteria Decision Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
1
0
2
Order By: Relevance
“…It is obvious that a goalkeeper who is agile, has strong reflexes and jumps very well will have a low chance of conceding a goal. In their study, Fleg and his colleagues concluded that the most important criteria for goalkeepers are handling, reflexes and jumping [ 63 ]. In another study, aerial ability, agility and anticipation are listed among the most important criteria [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is obvious that a goalkeeper who is agile, has strong reflexes and jumps very well will have a low chance of conceding a goal. In their study, Fleg and his colleagues concluded that the most important criteria for goalkeepers are handling, reflexes and jumping [ 63 ]. In another study, aerial ability, agility and anticipation are listed among the most important criteria [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spor okulu seçiminde olmasa bile ÇKKV tekniklerinin spor alanında kullanımları literatürde görülmektedir. Bireysel oyuncu performansını etkileyen birçok faktör olduğu için hem oyuncu performansını değerlendirmede hem de oyuncu seçiminde ÇKKV tekniklerinden yararlanılmıştır [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Aynı şekilde takımların performanslarını değerlendirmede de yine ÇKKV teknikleri kullanılmıştır [26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionunclassified
“…Kriter ağırlıklarını belirlerken ikili karşılaştırmalar ile göreceli önemi belirleyen SWARA metodu, AHP ve ANP (Analytic Network Process) gibi diğer yöntemlere göre daha az karşılaştırma içerip uzman görüşlerini almada kolaylık sağladığı için kullanılması tercih edilmiştir [40]. Alternatifleri sıralarken ise daha önce yaz spor okulu seçiminde [7] ve sporun çeşitli alanlarında alternatifleri sıralamak için [12,13,18,20,21,23,25,31,32,34,35,37,38] sıkça kullanılan TOPSIS yönteminin kullanılmasına karar verilmiştir. Yapılan literatür taramasında spor alanında SWARA ve TOPSIS metotlarının birlikte kullanıldığı hiçbir çalışmaya rastlanmazken, diğer alanlardaki çalışmaların ise az sayıda olduğu görülmüştür.…”
Section: Introductionunclassified